1959
DOI: 10.1136/hrt.21.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Iproniazid in the Treatment of Angina of Effort

Abstract: Iproniazid (a derivative of isoniazid) was originally introduced because of its antituberculous properties, but for some time it has been known to have several other effects, some of which may be due to the fact that it inhibits mono-amine oxidase, the enzyme responsible for the inactivation of serotonin (5 hydroxy-tryptamine) and adrenalin. Recently, Cesarman (1957) Unfortunately, neither series was controlled, and before accepting these results it is important that they be confirmed by more critical study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1

Year Published

1960
1960
1962
1962

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 1 publication
0
4
1
Order By: Relevance
“…Twelve (44%) patients improved with both tablets, so that a total of 23 (85%) patients improved on cavodil as compared with 13 (48 %) who improved on the control tablet. Though this trial was of short duration and on a small number of patients, the results contrast favourably with a similar recent trial in this department of iproniazid (Snow and Anderson, 1959). The improvemen in individual patients was often very striking, and the figures are encouraging, suggesting that cavodil may become a useful drug in the management of anginal pain.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Twelve (44%) patients improved with both tablets, so that a total of 23 (85%) patients improved on cavodil as compared with 13 (48 %) who improved on the control tablet. Though this trial was of short duration and on a small number of patients, the results contrast favourably with a similar recent trial in this department of iproniazid (Snow and Anderson, 1959). The improvemen in individual patients was often very striking, and the figures are encouraging, suggesting that cavodil may become a useful drug in the management of anginal pain.…”
Section: Discussioncontrasting
confidence: 58%
“…More recently, however, controlled trials have shown that the response to iproniazid may be little or no better than to a placebo (Dewar et al, 1959;Snow and Anderson, 1959). Moreover, it has unpleasant and sometimes serious side-effects, particularly when used for prolonged periods (Robitzek and Selikoff, 1952;Master, 1958;Towers and Wood, 1958;Benaim and Dixon, 1958).…”
mentioning
confidence: 99%
“…J. Med., 1958), and recent double-blind trials have shown no improvement of angina (Dewar et al, 1959;Snow and Anderson, 1959;Fife et al, 1960). Iproniazid inhibits monoamine oxidase, and the alleged effect on anginal pain was ascribed to this action.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, however, where the order of administering the tablets did not produce significantly different results, we have been unable to confirm their findings. In view of the considerable number of double-blind trials (Dewar et al, 1959;Snow and Anderson, 1959;Fife et al, 1960;Phear and Walker, 1960;Allanby et al, 1961;Murphy et al, 1961), in addition to this study, which have failed to confirm the value of the mono-amine oxidase inhibitors in the treatment of angina pectoris, it seems increasingly difficult to be convinced that earlier enthusiastic reports of improvement based on uncontrolled trials were not due to temporary changes in the mental outlook of the individual patients concerned or to natural variations in the symptoms of angina pectoris.…”
mentioning
confidence: 83%